Efficacy of Intravenous Lidocaine for Pain Relief in the Emergency Department: A Systematic Review and Meta-Analysis - Zhong, Junfeng; Hu, Junfeng; Mao, Linling; Ye, Gang; Qiu, Kai; Zhao, Yuhong; Hu, Shuangyan (Frontiers in Medicine, 2022)
Objective: To compare the efficacy of intravenous (IV) lidocaine with standard analgesics (NSAIDS, opioids) for pain control due to any cause in the emergency department. Methods: The electronic databases of PubMed, Embase, ScienceDirect, CENTRAL, and Google Scholar were explored from 1st January 2000 to 30th March 2021 and randomized controlled trials (RCTs) comparing IV lidocaine with a control group of standard analgesics were included. Results: Twelve RCTs including 1351 patients were included. The cause of pain included abdominal pain, renal or biliary colic, traumatic pain, radicular low back pain, critical limb ischemia, migraine, tension-type headache, and pain of unknown origin. On pooled analysis, we found no statistically significant difference in pain scores between IV lidocaine and control group at 15 minutes (MD: -0.24 95% CI: -1.08, 0.61 I2=81% p=0.59), 30 minutes (MD: -0.24 95% CI: -1.03, 0.55 I2=86% p=0.55), 45 minutes (MD: 0.31 95% CI: -0.66, 1.29 I2=66% p=0.53), and 60 minutes (MD: 0.59 95% CI: -0.26, 1.44 I2=75% p=0.18). There was no statistically significant difference in the need for rescue analgesics between the two groups (OR: 1.45 95% CI: 0.82, 2.56 I2=41% p=0.20), but on subgroup analysis, the need for rescue analgesics was significantly higher with IV lidocaine in studies on abdominal pain but not for musculoskeletal pain. On meta-analysis, there was no statistically significant difference in the incidence of side-effects between the two study groups (OR: 1.09 95% CI: 0.59, 2.02 I2=48% p=0.78). Conclusion: IV lidocaine can be considered as an alternative analgesic for pain control in the ED. However, its efficacy may not be higher than standard analgesics. Further RCTs with a large sample size are needed to corroborate the current conclusions.